2019
DOI: 10.3390/s19194269
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Laser Sensor (ILS) for Remote Surface Analysis: Application for Detecting Explosives in Fingerprints

Abstract: Here, we describe an innovative Integrated Laser Sensor (ILS) that combines four spectroscopic techniques and two vision systems into a unique, transportable device. The instrument performs Raman and Laser-Induced Fluorescence (LIF) spectroscopy excited at 355 nm and Laser-Induced Breakdown Spectroscopy (LIBS) excited at 1064 nm, and it also detects Laser Scattering (LS) from the target under illumination at 650 nm. The combination of these techniques supplies information about: material change from one scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…For example, the Raman peak heights can act as the weighting factors towards merge [ 24 ]. Taking PA as an example, we can set the weighting factors to be 0.07, 0.13, 0.14, 0.24, 0.19 for the images mapped at ~ 1050 cm −1 , ~ 1130 cm −1 , ~ 1300 cm −1 , ~ 1450 cm −1 and ~ 1630 cm −1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Raman peak heights can act as the weighting factors towards merge [ 24 ]. Taking PA as an example, we can set the weighting factors to be 0.07, 0.13, 0.14, 0.24, 0.19 for the images mapped at ~ 1050 cm −1 , ~ 1130 cm −1 , ~ 1300 cm −1 , ~ 1450 cm −1 and ~ 1630 cm −1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, other approaches relevant to the target, e.g., nanoenhanced laser-induced breakdown spectroscopy (NELIBS), are challenging to apply in numerous cases. For example, in remote LIBS measurements, the target is not only distant 10,11 but may also be in a hostile environment. 12 Besides, the addition of layers of nanoparticles onto the object's surfaces is prohibited in the case of cultural heritage and art.…”
Section: Introductionmentioning
confidence: 99%
“…, nano-enhanced laser-induced breakdown spectroscopy (NELIBS), are challenging to apply in numerous cases. For example, in remote LIBS measurements, the target is not only distant 10,11 but may also be in a hostile environment. 12…”
Section: Introductionmentioning
confidence: 99%
“…4,5 It has been reported that the complementary information provided by these two methods allows the identication of unknown terrestrial and extraterrestrial minerals. [6][7][8][9][10] Geology and space exploration further require the instrument to be used in situ and comprehensive analysis. Therefore, a dual spectroscopic platform, which is a hybrid between Raman and LIBS, is highly demanded.…”
Section: Introductionmentioning
confidence: 99%